Failure to Initiate Antiretroviral Therapy, Loss to Follow-up and Mortality Among HIV-Infected Patients During the Pre-ART Period in Uganda - Geng, Elvin H.; Bwana, Mwebesa B.; Muyindike, Winnie; Glidden, David V.; Bangsberg, David R.; Neilands, Torsten B.; Bernheimer, Ingrid; Musinguzi, Nicolas; Yiannoutsos, Constantin T.; Martin, Jeffrey N. (JAIDS Journal of Acquired Immune Deficiency Syndromes, 2013)
Background: Delays and failures in initiation of antiretroviral therapy (ART) among treatment eligible patients may compromise the effectiveness of HIV care in Africa. An accurate understanding, however, of the pace and completeness of ART initiation and mortality during the waiting period is obscured by frequent losses to follow-up. Methods: We evaluated newly ART-eligible HIV-infected adults from 2007 to 2011 in a prototypical clinic in Mbarara, Uganda. A random sample of patients lost to follow-up was tracked in the community to determine vital status and ART initiation after leaving the original clinic. Outcomes among the tracked patients were incorporated using probability weights, and a competing risks approach was used in analyses. Results: Among 2633 ART-eligible patients, 490 were lost to follow-up, of whom a random sample of 132 was tracked and 111 (84.0%) had outcomes ascertained. After incorporating the outcomes among the lost, the cumulative incidence of ART initiation at 30, 90, and 365 days after eligibility was 16.0% [95% confidence interval (CI): 14.2 to 17.7], 64.5% (95% CI: 60.9 to 68.1), and 81.7% (95% CI: 77.7 to 85.6). Death before ART was 7.7% at 1 year. Male sex, higher CD4 count, and no education were associated with delayed ART initiation. Lower CD4 level, malnourishment, and travel time to clinic were associated with mortality. Conclusions: Using a sampling-based approach to account for losses to follow-up revealed that both the speed and the completeness of ART initiation were suboptimal in a prototypical large clinic in Uganda. Improving the kinetics of ART initiation in Africa is needed to make ART more in real-world populations.
Keywords: Antiretroviral therapy; Africa; Loss to follow-up; Mortality